(untitled) (Research, Society and Development, 2025)
Rhythmic gymnastics is associated with a high aesthetic standard, which can create demands on athletes, especially young ones, to meet often harmful body standards. This research aimed to analyze the influence of body image and dietary profile in young gymnasts from the Escola Brasiliense de Ginástica Rítmica. The method used was quantitative and descriptive, and it was conducted with female athletes aged between 10 and 19 years. Three data collection instruments were used: the Food Frequency Questionnaire, to assess the consumption of certain foods by the gymnasts; the Body Shape Questionnaire (BSQ), to analyze the perception of body image; and the Silhouettes Scale, to compare the participants’ current and ideal body images. It was observed that the athletes consume highly processed and ultra-processed foods and exhibited a slight body distortion. It was found that multidisciplinary work in Rhythmic Gymnastics is of extreme importance. Nutrition, through food education, should demystify restrictive diets and promote healthy choices. Psychological support is essential to identify and prevent eating disorders and body image distortions early on. Investing in these actions from adolescence allows gymnasts to develop a healthy relationship with their bodies, promoting lasting physical and mental well-being. These initiatives ensure not only athletic performance but also the quality of life of the athletes in the face of the sport’s aesthetic and competitive pressures.